2006
DOI: 10.1207/s15327671espr1102_2
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Mathematics Achievement Gap in High-Poverty Middle Schools: Enablers and Constraints

Abstract: National and international comparisons have found that the mathematics achievement levels of US students fall far behind those of other developed nations, and that within the US itself, the students who are falling behind come predominantly from high poverty and high minority areas. This paper reports on a series of analyses that followed 4 cohorts of students from 3 such schools through the middle grades, 4 th to 8 th grade, where studies have found the mathematics achievement gap to develop most rapidly. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 8 publications
3
83
0
2
Order By: Relevance
“…to examining gains in standardized test performance is consistent with that of other research (Balfanz & Byrnes, 2006) and provides a mechanism for controlling for the particular nationally normed test used. Similarly, two additional variables indicating whether the student was performing at or above grade level (coded 1) or below grade level (coded 0) for the time of year when the test was administered were used.…”
Section: Methodssupporting
confidence: 76%
“…to examining gains in standardized test performance is consistent with that of other research (Balfanz & Byrnes, 2006) and provides a mechanism for controlling for the particular nationally normed test used. Similarly, two additional variables indicating whether the student was performing at or above grade level (coded 1) or below grade level (coded 0) for the time of year when the test was administered were used.…”
Section: Methodssupporting
confidence: 76%
“…In identifying significant classroom contextual factors for urban elementary youth, the results of this study can be used to develop policy and support interventions early in schooling. The focus on early school years is crucial for policy makers, as prior research has suggested that for urban students, missing school (i.e., full day absences) in early years of schooling has been found to be related to both diminished current and future educational outcomes, including lower testing performance, increased probability of grade retention, higher high school dropout rates, fewer employment opportunities, and greater chance of engaging in illegal activities (Alexander et al, 1997;Balfanz & Byrnes, 2006;Broadhurst et al, 2005;Gottfried, 2009Gottfried, , 2010Kane, 2006;Neild & Balfanz, 2006). Hence, documenting the effects of missing school for elementary school students will enable the early remediation of young urban students at risk for educational failure, before they enter into secondary education where the ramifications of missing school become increasingly harmful to the probability of both schooling and economic success.…”
Section: Ma Gottfriedmentioning
confidence: 99%
“…The dependent variables are the normal curve equivalent scores (NCE) for the Stanford Achievement Test (SAT9). The NCEs are the generally preferred measurement for methodological reasons -they have statistical properties that allow for evaluating achievement over time (Balfanz & Byrnes, 2006). Normal curve equivalents range in value from 1 to 99.…”
Section: Datamentioning
confidence: 99%
“…However, research has shown that students who know basic math facts can solve complicated math problems and are also more able to understand higher mathematical concepts (Stein, Kinder, Silbert, & Carnine, 2006). Finally, if a student does not have adequate math skills, this deficit has been linked to dropping out of school (Balfanz & Byrnes, 2006;Balfanz, Herzog, & MacIver, 2007;Lloyd, 1978) and later employment issues (Murnane, 2007;Murnane, Willett, Duhaldeborde, & Tyler, 2000;Murnane, Willett, & Levy, 1995).…”
Section: Introductionmentioning
confidence: 99%